2015
DOI: 10.1002/jts.22031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Peer Victimization and Posttraumatic Stress Among Primary School Children

Abstract: Peer victimization is a common stressor experienced by children. Although peer victimization has been studied extensively, few studies have examined the potential link between peer victimization and posttraumatic stress disorder (PTSD), and no studies of which we are aware have examined this link among children in primary school. The paucity of studies examining the link between PTSD and peer victimization in primary school is surprising because peer victimization occurs more frequently and is more likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
1
20
1
1
Order By: Relevance
“…Analyzing data from the 2014 National Survey of Children's Exposure to Violence, Finkelhor et al (2015) found that adding peer victimization to the original Adverse Childhood Experiences (ACE) Scale (Felitti et al, 1998) adds a substantial contribution to the prediction of mental health symptoms. This is coherent with our results, and with those of other studies that have identified peer victimization as a risk factor for developing a host of mental health symptoms (Litman, et al, 2015;Rosen et al, 2009;Smithyman et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analyzing data from the 2014 National Survey of Children's Exposure to Violence, Finkelhor et al (2015) found that adding peer victimization to the original Adverse Childhood Experiences (ACE) Scale (Felitti et al, 1998) adds a substantial contribution to the prediction of mental health symptoms. This is coherent with our results, and with those of other studies that have identified peer victimization as a risk factor for developing a host of mental health symptoms (Litman, et al, 2015;Rosen et al, 2009;Smithyman et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the wealth of studies on peer victimization, few studies have explored the potential links between negative experiences with peers and PTSD in school-aged children. One recent study has shown that children reporting peer victimization were twice as likely to show PTSD symptoms compared to children not victimized by their peers (Litman et al, 2015). Developing positive peer relationships is one of the major developmental tasks in middle childhood (Rubin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scores for each subscale ( Physical, Verbal, Social, and Vandalism ) are calculated by summing the corresponding items. The MPVS has demonstrated good internal reliability for each of its four subscales and has shown to be correlated with PTSD in children [ 71 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bullying involvement can be traumatic and may suggest traumatic exposure in other contexts (Carney, 2008;Crosby, Oehler, & Capaccioli, 2010;Idsoe, Dyregrov, Idsoe, 2012;Litman et al, 2015;Newman, Holden, & Delville, 2005). Treatment in the context of bullying and cyberbullying should therefore be sensitive to common trauma dynamics (Blitz & Lee, 2015;Mishna & Sawyer, 2011;Plumb, Bush, & Kersevich, 2016;Weaver, 2000).…”
Section: Prioritize Sensitivity and Responsiveness To Traumamentioning
confidence: 99%
“…Numerous studies have demonstrated high correlations between bullying involvement and psychological and social problems, suggesting that clinicians may encounter a disproportionate number of clients involved in bullying and cyberbullying, even if not the primary reason for referral and even if not identified. Indeed, victimized youth are more likely to meet the criteria for psychiatric diagnoses (Cuevas, Finkelhor, & Turner, 2011), including depression, anxiety, and other internalizing problems (Gladstone, Parker & Malhi, 2006;Kaltiala-Heino & Fröjd, 2011;Reijntjes, Kamphuis, Prinzie, & Telch, 2010;Ttofi, Farrington, Lösel, & Loeber, 2011), psychosomatic problems (Gini & Pozzoli, 2009), and post-traumatic stress disorder (PTSD) and other trauma symptoms (Carney, 2008;Idsoe, Dyregrov, Idsoe, 2012;Litman et al, 2015;Weaver, 2000). Symptoms secondary to bullying and cyberbullying experiences in childhood may persist into adulthood, along with disturbing memories of being victimized (Espelage, Hong, & Mebane, 2016;Miehls, 2017).…”
mentioning
confidence: 99%